Static Structural Simulation and Economic Feasibility of Hybrid Solar–Rainwater Rooftop Systems: A Case Study from Beirut, Lebanon - Kassem, Youssef; Camur, Huseyin; Al Halim, Osama Abed (Engineering, Technology & Applied Science Research, 2026)
Lebanon's energy and water crises, which include electrical shortages, comparatively high electricity prices, and water scarcity, are significant challenges. This study investigates the techno-economic and structural feasibility of a rooftop Photovoltaic (PV) and Rainwater (RW) collection system for a residential building in Beirut, considering the water and electricity crises. Accordingly, the feasibility of a 14.4 kW grid-connected PV system with and without battery storage was determined under average and extreme rainfall conditions. Structural feasibility showed a 35-degree angle of inclination, along with a relatively higher Factor of Safety (FOS) and lower weight, while the mechanical properties of galvanized steel and e-glass fiber were similar. The results demonstrate that Rainwater Harvesting (RWH) potential varied between 198 m³ in the average rainfall scenario and 1,558 m³ in the Maximum (Max.) rainfall case, constituting a valuable supplemental water supply. Additionally, the results indicate that the annual PV production was always considerably higher than demand, yielding substantial surplus energy, while around 60% of consumption falls at night, supporting the integration of modest battery storage. An economic evaluation showed a Levelized Energy Cost (LEC) of 0.244–0.271 USD/kWh for grid-connected operation with batteries, which yields favorable payback periods and strong life-cycle savings, even under Beirut's moderate solar irradiation. Consequently, this PV-RWH system is a dependable, financially feasible, and ecologically beneficial system for Lebanon that helps mitigate the shortages of electricity and water resources while promoting sustainable management.